Ultrasound-Guided Nerve Blocks for Flexor Tenosynovitis - John Bowling; Erick Zoumberakis (POCUS Journal, 2024)
Performing an ultrasound-guided nerve block (UGNB) is now common practice in many emergency departments (EDs) and is considered a core skill according to the American College of Emergency Physicians (ACEP). Nerve blocks are mostly utilized for fractures and laceration repairs, however, these blocks have many other applications. We present a case of utilizing an ulnar UGNB in a patient with flexor tenosynovitis and a history of intravenous drug use (IVDU) when parental opiates proved to be ineffective.